Audio Signal Processors - O'Neill,G; Germanovix,W; Toumazou,C (2007)
An audio signal processor includes a tone control ( 23 ). The tone control comprises two low-pass filters ( 221, 222 ) operating in current-mode and a subtractor ( 223 ) which subtracts the output currents of the filters to produce a band-pass characteristic. Each filter is a tuneable log-domain current-mode filter comprising MOS transistors operating in weak inversion. The tone control is useful in audio signal processors, hearing aids and single-channel and multi-channel Cochlear implants...